Comments and Corrections Correction to "Data-Aware Adaptive Pruning Model Compression Algorithm Based on a Group Attention Mechanism and Reinforcement Learning" - Yang, Zhi; Zhai, Yuan; Xiang, Yi; Wu, Jianquan; Shi, Jinliang; Wu, Ying (IEEE access, 2022)
In the above article [1] , unfortunately, we had missed grant number CQYC20200309237 of the funding organization Chongqing Talent Plan. This affected only the detail of the funding organization and had no influence on the discussion and conclusions in the article. The complete and correct funding organizations with grant number are as follows.